Device profile of the heartware HVAD system as a bridge-to-transplantation in patients with advanced heart failure: overview of its safety and efficacy. (2nd December 2019) - Mariani, Silvia; Hanke, Jasmin Sarah; Li, Tong; Merzah, Ali Saad; Chatterjee, Anamika; Deniz, Ezin; Haverich, Axel; Schmitto, Jan D.; Dogan, Günes
ABSTRACT: Introduction : Heart failure (HF) is one of the rising problems in the contemporary society with growing incidences of end-stage HF. While heart transplantation (HT) is the gold standard treatment for end-stage HF, its availability is limited by the lack of heart donors. As a consequence, left ventricular assist devices (LVADs) are becoming key therapies as bridge to transplant (BTT) strategy to improve survival and outcomes. Areas covered : A significant advancement for wider applications of LVADs as BTT was facilitated by the introduction of miniaturized pumps such as the HVAD (HeartWare®, Medtronic, MN, USA), allowing intrapericardial implants and less-invasive approaches. In this review article, we describe the technical features of the HVAD and its outcomes in terms of efficacy and safety when implanted as BTT strategy. Moreover, we discuss the postoperative results of HT in HVAD recipients and its application in the pediatric population. Expert opinion : It has been demonstrated that the HVAD positively influences the survival of end-stage HF patients awaiting HT, with an acceptable rate of adverse events. Due to its reduced size, it is particularly suitable for LVAD implantations through lateral thoracotomy and in patients with small thoracic dimensions.